"Track-Bridge" Interaction Problems in High Speed Bridge Design - Diachenko, Leonid; Benin, Andrey; Diachenko, Anastasia (International Journal of Engineering and Technology, 2018)
Track-bridge interaction problems have a main role in the design of bridges on high speed railways (HSR). In this paper, a technique is described for performing calculations of the interaction of the elements of the "bridge-jointless track" system. The complexity of these calculations lies in the nonlinear relationship between the bridge spans and the railway track. The characteristics of these relationships are largely determined by climatic factors (summer and winter conditions), as well as the presence of temporary loading on the bridge. The results of the interaction "bridge-jointless track" system are presented at temperature and train impacts for the characteristic types of bridge structures in the form of multi-span beams and continuous beams. The influence of the length, the construction scheme, the longitudinal stiffness of the intermediate supports on the magnitude of the forces arising in the rails of the continuous path is shown. Based on the performed calculations, conclusions were drawn about the characteristic modes of operation of the "bridge-jointless track" system and recommendations were made on constructive measures reducing efforts in rails.Â Â